Analysis of Drug Properties from Female Medicinal Formula using Cluster Analysis : A Case Study of Moh Krajang Yeemee - Jayathavaj, Vadhana; Judprakob, Chonlada; Yeemee, Boonyaporn (Health Science Journal of Nakhon Ratchasima College, 2022)
This exploratory documentary research had aimed to collect the female medicinal formulas of Moh Krajang Yeemee that used to treat menstrual related illnesses, and reversing analysis the properties of each drug from the properties of their formula using the cluster analysis. The results showed that: Moh Krajang Yeemee was the folk healer in Nakhon Si Thammarat who had been recognized for the treatment of women’s blood diseases during the period of 1957. A 200-page journal of drug formulas was written on the lined book and found 31 drug formulas consisted of 169 drugs for women from menstruation, childbirth and postpartum. The drugs were classified by Cluster Analysis according to the properties of their medicinal formulation into 8 groups of drugs with 15 properties, lead to determining which drug belongs to which drug group that have properties according to that group of formulation properties. The classified drugs can be used to determine the structure of the drug formula according to the Thai drug structure, which are straight drugs, auxiliary agents, compound drugs, tonic, flavoring, and coloring of the formula.